Quality Indicators for Evaluating Home Healthcare Services: A Scoping Review - Kianian, Toktam; Gholamnejad, Hanieh; Rassouli, Maryam; Farzadnia, Farzaneh; bagheriyeh, farzaneh; Kheibar, Nasrin; Moosavi, Soolmaz (Advances in Nursing & Midwifery, 2025)
Introduction: The elderly population’s doubling, the prevalence of chronic diseases, and the increase in the number of deaths constitute the current and the future image of global health. The increase in the demand for Home Health Care (HHC) has attracted the attention of not only governments, but also economic enterprises for the development of HHC centers. This study aims to investigate and collect HHC quality evaluation indicators in the existing studies through conducting a scoping review study. Methods: This study is a scoping review that investigates the extent of the research conducted in the field of HHC quality indicators and written based on the PRISMA-ScR Checklist. The inclusion criteria consisted of the study’s being written either in English or in Farsi, the study’s focusing on the structure and process of HHC monitoring or the results regarding HHC quality monitoring. Therefore, descriptive, multi methods and mix methods studies were included in the study. The search was conducted on studies that were published between January 1, 2000 to March 31, 2022. The data extracted from the included studies were re-examined by all the authors. The quality of extracted review studies was checked with PRISMA checklist, qualitative studies with COREQ and descriptive studies with STROBE checklist. Results: Out of 4977 extracted publications, 37 were finally included in the present study. Based on the findings of the included studies, HHC quality evaluation indicators were classified into three areas: structure (Appropriate physical space, equipment, and sufficient facilities- Effective document management system- Supply, and development of workforce), process (Patient-Centered Approach-Establishing safety and reliability- Efficient and timely support -Continuous Quality Improvement) and outcome (Functional Indicators-Clinical Indicators-Social indicators). Conclusions: This scoping review identified a comprehensive set of quality indicators for evaluating Home Healthcare (HHC), categorized into structure, process, and outcome domains. Common indicators include hospital readmission rates, unplanned emergency visits, functional status, symptom management, and patient satisfaction. Tools such as RAI-HC and OASIS are widely used for standardized assessment. The Efficiency Index (EI) helps compare service quality across HHC providers and informs policy decisions. Additionally, local, culturally-sensitive tools -especially for regions with religious considerations- should be developed and psychometrically validated. Ensuring appropriate infrastructure, effective documentation, and skilled workforce is also essential for quality care.